2015
DOI: 10.1016/j.metabol.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic high fat diet induces cardiac hypertrophy and fibrosis in mice

Abstract: Background Obesity can cause pathological changes in organs. We determined the effects of chronic high fat diet (HFD) and intermittent fasting, a paradigm providing organ protection, on mouse heart. Methods Seven-week old CD1 male mice were randomly assigned to control, HFD and intermittent fasting groups. Control mice had free access to regular diet (RD). RD was provided every other day to mice in the intermittent fasting group. Mice in HFD group had free access to HFD. Their left ventricles were harvested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 37 publications
(50 reference statements)
10
51
1
Order By: Relevance
“…As expected, with age OZR developed pathological cardiac hypertrophy and cardiac dysfunction concomitant with increased myocardial fat content, as well as apoptosis [4,5,6,7,27]. Similarly our data confirm the presence of cardiac hypertrophy in OZR and the preventive effect of AET on cardiac maladaptive morphological changes in OZRT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, with age OZR developed pathological cardiac hypertrophy and cardiac dysfunction concomitant with increased myocardial fat content, as well as apoptosis [4,5,6,7,27]. Similarly our data confirm the presence of cardiac hypertrophy in OZR and the preventive effect of AET on cardiac maladaptive morphological changes in OZRT.…”
Section: Discussionsupporting
confidence: 90%
“…Pathological cardiac hypertrophy and dysfunction associated with metabolic disorders have been reported in obesity [4,5,6]. The obese Zucker rat (OZR), a genetic model of morbid obesity, presents many of the same cardiovascular deficits noted in obese humans including myocardial hypertrophy [5,7], cardiac microvascular rarefaction [8], and exercise intolerance [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…41,42 While Masson's trichrome staining of tissue sections from WT and KO mice showed increased collagen depositions in the hearts of all HFD-fed animals, male and female KO HFD mice showed a much greater area of fibrosis compared to WT HFD mice. In addition, male WT HFD and KO HFD mice had larger accumulation of fibrotic tissue compared to females within the same experimental group (Fig.…”
Section: Cardiac Remodeling In Hfd-fed Atg7 Micementioning
confidence: 97%
“…Obesity is a prevalent risk factor for multiple disorders including insulin resistance, diabetes mellitus, some cancers (endometrial, breast and colon), and cardiovascular diseases (Cannon et al, 2016). Among the cardiovascular diseases, obesity-related cardiac hypertrophy (ORCH), cardiomyopathy, and even heart failure, were often reported (Wang et al, 2015, Zhang et al, 2015b. Previously, the majority of the research has focused on the effects of obesity on the adulthood's health, morbidity and mortality (Abdurrachim et al, 2014, Leopold, 2015 however, in recent years, childhood obesity has been demonstrated as a significant health issue.…”
Section: Introductionmentioning
confidence: 99%